DEVELOPMENT OF MULTIMEDIA LEARNING SOLUTION MATHEMATICS (MUJAMATCAH) AS A LEARNING MEDIA FOR GRADE IV PRIVATE SCHOOL STUDENTS - Wahyu Fitri Andriani; Desy Dwi Riana; Dwi Kameluh Agustina (Universitas Islam Balitar, 2021)
The development of technology is currently very fast and influences various fields, one of which is education. for example the use of media in learning, such as the use of multimedia learning. In addition, this study also aims to improve students' understanding of fraction material for fourth grade elementary school students. This is the background of this research in multimedia learning mathematics development. The purpose of this study was to develop multimedia learning mathematics on fractions for fourth grade elementary school students. This research is a Research and Development (RnD) type of research according to Sugiyono which is limited to only seven stages of research. The stages include, potentials and problems, data collection, product design, design validation, design revision, product testing, and product revision. The result of this research is multimedia learning of fraction mathematics (Mujamatcah) for fourth grade elementary school students with the aim of increasing students' understanding. Where to get the following results, for the validation of material experts 94% (very feasible), validation of media and multimedia experts for learning 87% (feasible), and validation of language 89% (feasible). The results obtained from the student readability test obtained data of 96% (very feasible) and for teacher readability of 91% (very feasible).